CAN bus risk analysis revisit - Mansor, Hafizah; Markantonakis, Konstantinos; Mayes, Keith (Springer, 2014)
In automotive design process, safety has always been the main concern. However, in modern days, security is also seen as an important aspect in vehicle communication especially where connectivity is very widely available. In this paper, we are going to discuss the threats and vulnerabilities of a CAN bus network. After we have considered a number of risk analysis methods, we decided to use FMEA. The analysis process allowed us to derive the security requirements of a CAN bus. Experimental setup of CAN bus communication network were implemented and analysed.